Oral Isotretinoin for Refractory Cutaneous Pseudolymphoma: A Case Report - Tangkijngamvong, Natsinee; Pongprutthipan, Marisa (Thai Journal of Dermatology, 2023)
Cutaneous pseudolymphoma is a benign lymphoproliferative disorder that can mimic cutaneous lymphoma’s clinical and histological features. While spontaneous resolution is observed in some cases, others may exhibit a persistent or recalcitrant clinical course. In such instances, alternative therapeutic options become imperative. Here, we present a case of an 83-year-old female with erythematous plaques on the right cheek. The pathological examination confirmed the diagnosis of cutaneous pseudolymphoma, with a history of recalcitrant to various treatment modalities. Oral isotretinoin was initiated as a monotherapy, and skin lesions were resolved within a few weeks without significant adverse events. This case report aims to provide additional evidence supporting the efficacy of isotretinoin as a viable treatment option for refractory cutaneous pseudolymphoma.